2006
DOI: 10.1016/s0022-5347(05)00179-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Transabdominal Pyeloplasty in Children is Feasible Irrespective of Age

Abstract: Laparoscopic transabdominal dismembered pyeloplasty is effective and safe in infants and children. The feasibility is also excellent in patients younger than 1 year. The transabdominal approach revealed good exposition without a disadvantage for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 20 publications
7
78
0
8
Order By: Relevance
“…It has been shown that LP is a good treatment option for both very young children (< 1 year) and for elderly people (70 years or older). 23,24 LP has also been shown to be adequate treatment for patients with UPJO in horseshoe kidneys. 25 In large studies the outcomes of LP are very good, ranging from 85 to 100%.…”
Section: Laparoscopic Pyeloplasty (Lp)mentioning
confidence: 99%
“…It has been shown that LP is a good treatment option for both very young children (< 1 year) and for elderly people (70 years or older). 23,24 LP has also been shown to be adequate treatment for patients with UPJO in horseshoe kidneys. 25 In large studies the outcomes of LP are very good, ranging from 85 to 100%.…”
Section: Laparoscopic Pyeloplasty (Lp)mentioning
confidence: 99%
“…The disadvantage of LP is that operative times are significantly higher than open pyeloplasty 11,12 . In particular, laparoscopic suturing particularly for children is challenging and time-consuming and requires a learning curve 11 , however, it significantly improved, even with pediatric LP, with increased experience in previous reports 11,13 .Open pyeloplasty is performed through the retroperitoneal approach, which has the advantage of less risk of intraperitoneal organ injury, postoperative ileus, and avoidance of potential deleterious effects of peritoneal exposure to blood and urine. Although adhesions may occur with urological laparoscopic procedures, the incidence appears lower than would be expected with open exploration 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Although adhesions may occur with urological laparoscopic procedures, the incidence appears lower than would be expected with open exploration 14 . Laparoscopic dismembered pyeloplasty is an acceptable option for UPJO in infants and younger children [13][14][15] . A recent report has demonstrated that laparoscopic dismembered pyeloplasty is technically possible in infants younger than 6 months 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations